New insight into arginine and tryptophan metabolism in macrophage activation during tuberculosis - Zhang, Kangling; Mishra, Abhishek; Jagannath, Chinnaswamy (Frontiers in Immunology, 2024)
Arginine and tryptophan are pivotal in orchestrating cytokine-driven macrophage polarization and immune activation. Specifically, interferon-gamma (INF-γ) stimulates inducible nitric oxide synthase (iNOS) expression), leading to the conversion of arginine into citrulline and nitric oxide (NO), while Interleukin-4 (IL4) promotes arginase activation, shifting arginine metabolism toward ornithine. Concomitantly, INF-γ triggers indoleamine 2,3-dioxygenase 1 (IDO1) and Interleukin-4 induced 1 (IL4i1), resulting in the conversion of tryptophan into kynurenine and indole-3-pyruvic acid. These metabolic pathways are tightly regulated by NAD + -dependent sirtuin proteins, with Sirt2 and Sirt5 playing integral roles. In his view, we present novel insights that augment our understanding of the metabolic pathways of arginine and tryptophan following Mycobacterium tuberculosis infection, particularly their relevance in macrophage responses. Additionally, we discuss arginine methylation and demethylation and the role of Sirt2 and Sirt5 in regulating tryptophan metabolism and arginine metabolism, potentially driving macrophage polarization.